The Reading Exercises in the English Students’ Book Entitled “Interactive English” for Grade VIII Students - Ryan Purnomo (Faculty of Education Universitas Nahdlatul Ulama Yogyakarta, 2023)
The textbook is one of the materials in teaching learning process which is regularly used by both teachers and students at school. Textbooks should improve the quality of teaching and learning process. The purpose of this study is to find whether or not the materials provided in the English textbook “Interactive English” designed for the eight grade of Junior high school compatible with the curriculum 2013. In this research, besides book, the researcher also used data sheets, internet and information. To facilitate students in developing their reading ability, the textbook provides five types of reading questions, namely multiple choice question, matching question, essay question, short answer question, and completion items very good category. These types of questions measure how much students understand from the reading texts. In collecting data, the researcher used documentation study by the following steps, as follows; 1) list the suggested criteria for evaluating textbook. 2) list the criteria of reading exercise suggested 3) read the English student book entitled Interactive English., 4) find out the reading exercises provided in the textbook, 5) classify them based on the criteria of reading exercise suggested by Na’ima Mosa Ali. The data is analyzed by using a descriptive qualitative method. The researcher used the steps of analyzing data as stated by The data collected for this study will be gathered from the English textbook “Interactive English” published by Yudhistira. By using this book, the students can understand the materials easily. __________________________________________________________________________________________________________________________________ Buku teks merupakan salah satu bahan dalam proses belajar mengajar yang sering digunakan baik oleh guru maupun siswa di sekolah. Buku teks harus meningkatkan kualitas proses belajar mengajar. Tujuan dari penelitian ini adalah untuk menemukan apakah materi yang disediakan dalam buku teks bahasa Inggris “Interactive English” yang dirancang untuk kelas delapan SMP sesuai dengan kurikulum 2013. Dalam penelitian ini, selain buku, peneliti juga menggunakan lembar data. , internet dan informasi. Untuk memudahkan siswa dalam mengembangkan kemampuan membaca, buku teks menyediakan lima jenis soal bacaan, yaitu soal pilihan ganda, soal menjodohkan, soal esai, soal isian singkat, dan soal penyelesaian soal kategori sangat baik. Jenis pertanyaan ini mengukur seberapa banyak pemahaman siswa dari teks bacaan. Selain itu, peneliti harus memahami tentang evaluasi materi terutama dalam latihan. Dalam pengumpulan data, peneliti menggunakan studi dokumentasi. Proses pengumpulan data dilakukan dengan langkah-langkah sebagai berikut; 1) daftar kriteria yang disarankan untuk mengevaluasi buku teks. 2) menyebutkan kriteria latihan membaca yang disarankan oleh Na'ima Mosa Ali, 3) membaca buku siswa bahasa Inggris berjudul Interactive English., 4) mengetahui latihan membaca yang tersedia di buku teks, 5) mengklasifikasikannya berdasarkan kriteria bacaan latihan disarankan oleh Na'ima Mosa Ali. Data dianalisis dengan menggunakan metode deskriptif kualitatif. Peneliti menggunakan langkah-langkah analisis data seperti yang dikemukakan oleh Spreadley. Data yang dikumpulkan untuk penelitian ini akan dikumpulkan dari buku teks Bahasa Inggris “Interactive English” yang diterbitkan oleh Yudhistira. Dengan menggunakan buku ini, siswa dapat memahami materi dengan mudah